1990
DOI: 10.1016/0020-7292(90)90009-a
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian fibroma — clinical and histopathological characteristics

Abstract: Twenty-three cases of ovarian fibroma, comprising 3% of all benign tumors seen over a 20-year period, were analyzed. It was unilateral in all cases affecting more commonly the left ovary (70%). Whilst a majority of cases (77%) were encountered in the reproductive age group, the tumor was rare before the second decade. Only in 13% of cases was ascitis clinically detectable. This was not influenced by the size and weight (average of 9.3 x 10.8 x 11.1 cm and 959 g, respectively) of the tumors; a smooth-surfaced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
3
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 8 publications
4
59
3
3
Order By: Relevance
“…The treatment of ovarian fibroma has always been surgical, which comprises removal of tumor followed by intraoperative frozen section [8,9]. Our study has demonstrated a very good correlation between frozen section and final histopathological diagnosis of ovarian fibroma.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The treatment of ovarian fibroma has always been surgical, which comprises removal of tumor followed by intraoperative frozen section [8,9]. Our study has demonstrated a very good correlation between frozen section and final histopathological diagnosis of ovarian fibroma.…”
Section: Discussionmentioning
confidence: 54%
“…In all post-menopausal women and those who have completed their family, total abdominal hysterectomy (TAH) is the treatment of choice; however, owing to benign nature of the disease, a fertility-preserving surgery with unilateral salpingo-oophorectomy in young premenopausal women can be contemplated [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is the commonest subtype of the sex cord-stromal tumors [2]. The mean age at diagnosis is 48 years and 90% of patients are at least 30 years old when they are diagnosed with fibroma [3]. In our case patient was 22 years old.…”
Section: Discussionmentioning
confidence: 59%
“…Occasionally large fibromas may develop a pedicle and undergo torsion causing acute abdominal symptoms as in the present case. Ascites or classic Meig's syndrome with additional hydrothorax has been found in 10% of all cases and 40% of tumors larger than 10 cm in maximum diameter [3]. Development of …”
Section: Discussionmentioning
confidence: 99%
“…They can manifest with abdominal enlargement, urinary symptoms, abdominal pain and occasionally torsion. [1][2][3] Ovarian torsion is usually associated with significant pain. This lady only had minimal pain despite the large size and necrotic changes due to torsion.…”
Section: Discussionmentioning
confidence: 99%